CLIMATE STRUGGLE AND IDEOLOGY IN MACRON’S SPEECHES (2024–2025): AN ECO-CRITICAL ANALYSIS - Anggeli Trisna Mekar Tiara; Marliza Arsiyana (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2026)
This study investigates how climate struggle and ecological ideology are constructed in four speeches delivered by Emmanuel Macron (2024–2025) using an eco-critical discourse analysis framework within Fairclough's (1992) three-dimensional model, Halliday & Matthiessen’s (1994) ideational metafunction, Stibbe's (2015) ecolinguistic model, and Corbett's (2006) environmental ideology. The global environmental crisis is one of the greatest challenges facing humanity today. Despite the growing body of critical discourse studies on climate communication, little attention has been paid to how French leadership constructs ecological ideology in international forums. This research employs a qualitative approach, with the research data comprising the discourse on the fight against climate change in Emmanuel Macron’s speeches. The results showed that the climate struggle is dominated by material processes, with France and Western institutions positioned as the primary agents of global climate action. The ideology identified across the four speeches is conservationism, wherein nature is valued for its benefits to humanity rather than for its intrinsic value. Yet, through the eco-linguistic lens of ecosophy, Macron's discourse occurs as ambivalent, which reflects a sincere ecological commitment that nonetheless remains rooted in a neoliberal framework. Thus, it prioritizes private financing, market mechanisms, and technocratic governance.